Model Kepemimpinan Nehemia Berbasis Pengelolaan Bagi Pengelolaan Organisasi Gereja - Bandhaso, Silas (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2024)
The role of a leader in an institution, be it secular or spiritual, has great significance. They are not only the commanders who direct subordinates, but also act as organizers who ensure the smooth running of activities. Leaders have the ability to influence others. The purpose of this study is to discover how Nehemiah's management as a leader was able to complete the construction of the wall of Jerusalem. Although various challenges were faced during the construction of the Jerusalem wall, in the end the construction of the wall could be completed properly. The method used is library research method. The results of this study show that the management carried out by Nehemiah so that he was able to rebuild the walls of Jerusalem well was the management of human resources, conflict management, and management of motivation.